Variation in organic crystallite unit for different rank Indian coals by X-ray diffraction. (11th May 2022) - Jaiswal, Yash; Pal, Sunder Lal; Kush, Lav; Jaiswal, Harsh
To improve the utilisation of Indian coals more efficiently, chemical and physical reactions between the coal and different reactants need to be established during its use. In view of this, assessment of different structural features of low-high rank Indian coals was performed. The detailed investigation and structural difference between four different rank Indian coals were obtained using XRD. Important structural parameters of heterogeneous coal sample like aromaticity, degree of disorder index, amorphous carbon fraction moreover size of crystallite with their distribution parameters like interplanner lamellar distance, crystallite height and diameter, lamellar counts were determined. The results show that coal rank, carbon content and vitrinite mean reflectance are the main parameters which controls the structure of the organic crystallite unit in coal. The variation of structural parameters with all three controlled variables is presented in this paper. This knowledge is helpful in improvising methods for the use of coal. [Received: March 27, 2021; Accepted: September 24, 2021]